Saprolegnia milanezii sp. nov., a new species of Saprolegniales (Oomycota, Straminipila) from Brazil - Rocha, Sarah Cristina Oliveira; Sandoval-Sierra, Jose V.; Diéguez-Uribeondo, Javier; Gonçalves, Danilo R.; Jerônimo, Gustavo H.; Jesus, Ana L. De; Marano, Agostina V.; Pires-Zottarelli, Carmen L. A. (Phytotaxa, 2016)
Saprolegnia milanezii sp. nov. is described as a new species of the genus Saprolegnia (Saprolegniales, Oomycota). It has been collected from freshwater samples at “Parque Estadual da Ilha do Cardoso”, Cananéia, São Paulo State, Brazil. This species is characterized by rare antheridia, extended stalk near the oogonial septum and subcentric oospores. Phylogenetic analysis using concatenated ITS and LSU rDNA regions confirmed the position of this new species into the genus Saprolegnia as sister group of S. furcata.